The Relationship Between Noise Exposure and Hearing Loss (Case Study at discotheque A, B, C in Medan) - Naek Silitonga (Pre Cure, 2014)
Aim: To determine the correlation between noise exposure levels and noise-induced hearing loss in employees ( case study of discotheque A, B, C in Medan).Method: This study used analytic cross-sectional study design. The data obtained through interview process, otoscopic examination and pure tone audiometry.Result: The noise-exposed employees (>85 dB) were 110 people (100%). Audiometric examinations towards the inclusion-fulfilled criteria employees were 51 (46,6%) non hearing-impaired employees and 59 (53,6%) hearing-impaired employees.Conclusion and Recommendation: There is a significant correlation between noise exposure levels and hearing function in employees of several discotheques in Medan. It is important for the employees to protect their ears.Keywords : Noise-induced hearing loss, employee, discotheque.